Benzene and sulfide removal from groundwater treated in a microbial fuel cell. Issue 12 (3rd July 2013) - Rakoczy, Jana; Feisthauer, Stefan; Wasmund, Kenneth; Bombach, Petra; Neu, Thomas R.; Vogt, Carsten; Richnow, Hans H.
Abstract Sulfidic benzene‐contaminated groundwater was used to fuel a two‐chambered microbial fuel cell (MFC) over a period of 770 days. We aimed to understand benzene and sulfide removal processes in the anoxic anode chamber and describe the microbial community enriched over the operational time. Operated in batch feeding‐like circular mode, supply of fresh groundwater resulted in a rapid increase in current production, accompanied by decreasing benzene and sulfide concentrations. The total electron recoveries for benzene and sulfide were between 18% and 49%, implying that benzene and sulfide were not completely oxidized at the anode. Pyrosequencing of 16S rRNA genes from the anode‐associated bacterial community revealed the dominance of δ‐Proteobacteria (31%), followed by β‐Proteobacteria, Bacteroidetes, ϵ‐Proteobacteria, Chloroflexi, and Firmicutes, most of which are known for anaerobic metabolism. Two‐dimensional compound‐specific isotope analysis demonstrated that benzene degradation was initiated by monohydroxylation, probably triggered by small amounts of oxygen which had leaked through the cation exchange membrane into the anode chamber. Experiments with [13C6]‐benzene revealed incorporation of 13C into fatty acids of mainly Gram‐negative bacteria, which are therefore candidates for benzene degradation. Our study demonstrated simultaneous benzene and sulfide removal by groundwater microorganisms which use an anode as artificial electron acceptor, thereby releasing an electrical current. Biotechnol. Bioeng. 2013;110: 3104–3113. © 2013 Wiley Periodicals, Inc.